Recent Research and Theory on Market in Sociology; A Semi-Systematic Literature Review - Firdaus Firdaus; Zusmelia Zusmelia (Jurnal Economia, 2023)
AbstractCurrent studies of market use social science theories and offer new theoretical approaches. This article discusses the latest theories and approaches to analyze the market. This research was conducted with semi-systemic literature review approach. The data is obtained through searching the published article in online scientific journals related to the market. Data analysis was carried out by thematically categorizing the finding and the presented descriptively. The results found two categories of approaches in the study of markets, namely Structural and Performative (consisted of institutional, network, cultural and normative approaches), and an integrative approach (consisted of integration of social forces and neo-institutionalism in sociology). This paper argues that current theories tend to analyze the market towards stability than dynamics, and the market system than the marketplace. Therefore, this paper purpose a suitable theoretical approach to understand market stability, dynamics and the market as a market place and a market system simultaneously.Keywords:Market Place, Market System, Economic Sociology, Sociology of Market